The system of work on Schevchenko’s literary works in teaching Ukrainian as a foreign language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to the actual problem of teaching methodology of the Ukrainian language to foreign students . An ability to read original literary works is a prerequisite of complex and comprehensive work aimed at learning Ukrainian as a foreign language. Introducing students to Ukrainian classical literature basing on Taras Shevchenko’s poetic legacy as an example will contribute to the process of forming students’ skills and abilities to understand culturally orientated texts.
Keywords: art works; Ukrainian classical literature; Taras Shevchenko’s poetic legacy; translated works